CONSTRUCTION OF BINH DUONG PROVINCE IN THE WAY OF SMART CITY - Toan, Trần Thanh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Building smart cities has become an unavoidable trend in the world’s cities and metropolitan areas. Building and constructing a smart city or smart city is crucial in Vietnam in general, and in Binh Duong province in particular, to successfully take advantage of the potential of the fourth industrial revolution (Industry 4.0). and in the direction of long-term development Building and developing a smart city or smart city has been clearly identified as one of the three core contents in actively participating in Industry 4.0, alongside developing the digital economy and building an e-Government moving towards a digital government, so developing a smart city or smart city is a must-do in the current time for Binh Duong province. Building a smart city is unavoidable, but it is not an easy task. Each city faces its own set of problems, necessitating the use of and combining a variety of remedies.enges, and therefore needs to use and combine many specific solutions.